Halogenase‐Inspired Oxidative Chlorination Using Flavin Photocatalysis - Hering, Thea (Angew Chem Int Ed Engl, 2016)
Chlorine gas or electropositive chlorine reagents are used to prepare chlorinated aromatic compounds, which are found in pharmaceuticals, agrochemicals, and polymers, and serve as synthetic precursors for metal‐catalyzed cross‐couplings. Nature chlorinates with chloride anions, FAD‐dependent halogenases, and O(2) as the oxidant. A photocatalytic oxidative chlorination is described based on the organic dye riboflavin tetraacetate mimicking the enzymatic process. The chemical process allows within the suitable arene redox potential window a broader substrate scope compared to the specific activation in the enzymatic binding pocket.